2016
DOI: 10.1038/srep33647
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-related proteins are functionally active in human spermatozoa and may be involved in the regulation of cell survival and motility

Abstract: Macroautophagy (hereafter autophagy) is an evolutionarily highly conserved cellular process that participates in the maintenance of intracellular homeostasis through the degradation of most long-lived proteins and entire organelles. Autophagy participates in some reproductive events; however, there are not reports regarding the role of autophagy in the regulation of sperm physiology. Hence, the aim of this study was to investigate whether autophagy-related proteins are present and functionally active in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 83 publications
8
75
0
2
Order By: Relevance
“…TOM20 and VDAC are mitochondrial member proteins. TOM20 quantification is widely performed to monitor mitochondrial mass during mitophagy, [31] and VDAC1 degradation by ubiquitination is associated with mitophagy. [32] IHC revealed notably decreased TOM20 expression in the tubules of db/db mice compared to those of controls, and mitoQ treatment reversed this change (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TOM20 and VDAC are mitochondrial member proteins. TOM20 quantification is widely performed to monitor mitochondrial mass during mitophagy, [31] and VDAC1 degradation by ubiquitination is associated with mitophagy. [32] IHC revealed notably decreased TOM20 expression in the tubules of db/db mice compared to those of controls, and mitoQ treatment reversed this change (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[21], [42], [43] In this study, we used the mitochondria-targeted antioxidant mitoQ to overcome this limitation. [21], [31] Pre-treatment with mitoQ alleviated tubular damage in db/db mice, a change reflected by deceases in the levels of tubular injury markers, such as β-NAG. Notably, mitochondrial oxidative stress, mitochondrial fragmentation and mitochondrial dysfunction amelioration were accompanied by lower apoptosis levels in tubular cells under hyperglycemic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that many ATG proteins like LC3, ATG5, PINK1, and p62 are highly expressed in human spermatozoa, especially in the middle piece of the tail where mitochondria are located (Aparicio et al ., ). Autophagy is thought to be crucial for sperm survival and motility.…”
Section: The Roles Of Autophagy In the Mammalian Life Cyclementioning
confidence: 97%
“…autophagy was reported to be capable of protecting the function and integrity of sertoli cells by inhibiting the ectoplasmic specialization degradation. Additionally, autophagy was shown to be related to proteins that play a critically role in human sperm, and so the mitophagy (a form of autophagy) may affect different aspects of sperm function . A single examination is sufficient to determine that autophagy is an active process in sperm, and its activation may critically affect the regulation of sperm physiology and also the maintenance of viability and motility .…”
Section: Discussionmentioning
confidence: 99%